The Role of Gratitude in Enhancing Psychological Well-Being in Adolescent Development: An Integration of Psychological and Islamic Perspectives - ubaidah, ade (Asian Journal of Islamic Psychology, 2025)
This paper explores the role of gratitude in enhancing psychological well-being, bridging insights from psychological research and Islamic teachings. Gratitude, a fundamental virtue, has been extensively studied for its positive effects on mental health, particularly among adolescents and young adults. Empirical evidence links gratitude to increased life satisfaction, happiness, and emotional well-being. From an Islamic perspective, gratitude, or shukr, fosters spiritual resilience and psychological strength. It is viewed not only as a response to divine blessings but also as a proactive practice that nurtures positive emotions, reinforces coping strategies, and encourages prosocial behavior. This paper reviews significant studies, including gratitude-based interventions such as journaling and gratitude letters, demonstrating their efficacy in reducing depression, anxiety, and stress while fostering long-term well-being. Cultural and gender differences in gratitude expression and their implications for mental health are also discussed. Furthermore, integrating gratitude into counseling and therapeutic practices, particularly within the Islamic psychological framework, is highlighted as a promising approach. The findings suggest that cultivating gratitude can serve as an effective strategy for enhancing mental health, providing valuable insights for developing therapeutic interventions that align with both psychological principles and Islamic values.